Analysis of cis-isomer-enriched dihydroquercetin sample by 1D and 2D NMR spectroscopy - R. P. Terekhov; A. Taldaev; E. V. Bocharov; D. I. Pankov; A. D. Savina; I. A. Selivanova (Разработка и регистрация лекарственных средств)
Introduction. The structure of dihydroquercetin (DHQ) is characterized by two chiral centers at positions 2 and 3 of the benzopyran cycle, resulting in possible diastereomers: trans- and cis-isomers. Therefore, the development of methods for qualitative and quantitative control of DHQ diastereomers in analyzed samples is essential for patient safety management. Nuclear magnetic resonance (NMR) spectroscopy is one of the physicochemical methods that can be used for this purpose.Aim. The study objective was to accumulate the analytical and structural characteristics of cis-DHQ by NMR spectroscopy of the spheroidal form of this flavonoid (DHQs).Materials and Methods. 1D 1H, 1H,1H-COSY, 1H,1H-NOESY, and 1H,13C-HSQC NMR spectra were acquired at 298 K on an 800 MHz NMR spectrometer equipped with a TXI triple resonance probe. The number of scans was 32. The mixing time in the NOESY experiment was 400 ms. The 1H and 13C were analyzed using CcpNmr software. The dihedral angles were calculated by applying the Karplus equation.Results and discussion. In trans-DHQ, the chemical shift values for H2 and H3 are 4.93 ppm and 4.52 ppm, respectively, and in cis-DHQ they are 5.31 ppm and 4.20 ppm, respectively. The spin-spin coupling constants between H2 and H3 of trans- and cis-DHQ are 12.00 Hz and 2.40 Hz, respectively. Thus, the dihedral angles for the trans- and cis-isomers are 154° and 64°, respectively. We found that DHQs contains 12.5 % of the cis-isomer.Conclusion. Our experiments confirmed that NMR spectroscopy can discriminate between trans- and cis-DHQ based on the chemical shift values for the cross-peaks of H2 and H3. The second major finding was that this method can be considered as a more selective quantitative analysis than HPLC with UV detection without reference. One of the most important results of this study for drug development is the updated information on the structural parameters of DHQ diastereomers in the liquid phase.